Assessment of mineral and biochemical profiles, feed and milk composition of dairy cattle in cold arid Kargil, Ladakh - Beigh, Yasir Afzal; Asgar Ali; Abdul Majeed Ganai; Javid Farooq (Indian Journal of Dairy Science, 2026)
Mineral imbalances in livestock impair health, productivity, and reproduction, altering blood metabolites and milk composition in dairy animals. Thus, evaluation of regional mineral status is essential which requires assessment of mineral content of available feedstuffs offered to them, and other factors such as physiological state (pregnancy and lactation), production level (milk yield) etc. This study was conducted to find out the mineral profile of some important feedstuffs and plasma of dairy cattle along with their metabolic parameters and milk composition under farmers’ field condition in district Kargil. A total of 129 blood and 102 milk samples were collected randomly from dairy cattle in 6 blocks (Zanskar, Sankoo, TSG, Kargil, Drass and Chiktan) of the district. These samples were divided into three groups based on milk yield of animals as cattle yielding milk 5-10 kg/day, upto 5 kg/day and dry pregnant. Also, samples of feeds and fodders most commonly offered to livestock by the dairy farmers were collected separately, pooled block wise and analysed. The chemical composition of the feedstuffs were within prescribed normal ranges except wild grass hay in which content of most of the minerals were below the critical levels. The concentrate feeds contained adequate levels of all the nutrients and minerals with low P and Mn contents in apricot oilcake. All plasma macro-minerals and only Fe and Co among micro-minerals were above the critical levels across all the milk yield groups of dairy cattle throughout the district. Overall deficiency of Ca, P and Na among macro- and Cu, Zn and Mn among micro-minerals exists among 45.73, 31.78, 44.96, 64.34, 86.04, 72.86%, respectively in blood plasma of dairy cattle in the district with higher (p